Studi Literatur Tekanan Kerja Di Perusahaan Audit - Adanan Silaban; Manatap Berliana Lumban Gaol; Meilinda Stefani Harefa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Work pressure is a demand in the work environment that can cause individuals to experience stress, and subsequently can have an impact on individual attitudes, intentions and behavior in carrying out tasks. In the audit firm's work environment, auditors may experience pressures that have an impact on the attitudes, intentions and behavior of the auditors in implementing the audit program; and can further affect audit quality.This article aims to describe and discuss various forms of potential pressure within audit firms and their impact on auditor behavior in implementing audit programs. To achieve this goal, the general model of job stress is used as a framework to build a model of stress in the audit firm's work environment. A review of previous research in this area is presented, and directions for future research are presented. Keywords: Pressure, Stress, Auditor Behavior